Novel Action of FSH on Stem Cells in Adult Mammalian Ovary Induces Postnatal Oogenesis and Primordial Follicle Assembly. (9th November 2015) - Bhartiya, Deepa; Parte, Seema; Patel, Hiren; Sriraman, Kalpana; Zaveri, Kusum; Hinduja, Indira
Abstract : Adult mammalian ovary has been under the scanner for more than a decade now since it was proposed to harbor stem cells that undergo postnatal oogenesis during reproductive period like spermatogenesis in testis. Stem cells are located in the ovary surface epithelium and exist in adult and menopausal ovary as well as in ovary with premature failure. Stem cells comprise two distinct populations including spherical, very small embryonic-like stem cells (VSELs which express nuclear OCT-4 and other pluripotent and primordial germ cells specific markers) and slightly bigger ovarian germ stem cells (OGSCs with cytoplasmic OCT-4 which are equivalent to spermatogonial stem cells in the testes). These stem cells have the ability to spontaneously differentiate into oocyte-like structures in vitro and on exposure to a younger healthy niche. Bone marrow may be an alternative source of these stem cells. The stem cells express FSHR and respond to FSH by undergoing self-renewal, clonal expansion, and initiating neo-oogenesis and primordial follicle assembly. VSELs are relatively quiescent and were recently reported to survive chemotherapy and initiate oogenesis in mice when exposed to FSH. This emerging understanding and further research in the field will help evolving novel strategies to manage ovarian pathologies and also towards oncofertility.